2002
DOI: 10.1080/10915810290096342
|View full text |Cite
|
Sign up to set email alerts
|

Chromium Toxic Effect Monitoring Using Ozonation Method

Abstract: The hexavalent chromium toxicity (in vitro) to plasma, erythrocytes, and semen lipids was evaluated. The ozonation technique is suggested to realize the rapid measurements of the lipid peroxidation (LPO) by means of the double bond indexes (DB-index and DB(cell)-index) calculation. The obtained experimental results permit to conclude that it is possible to detect the chromium effect on LPO by ozonation. The DB-index and DB(cell)-index determination in the plasma, erythrocytes, and sperm can be considered as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The largest increase in DBI found for roots of Quila 66304, compared to roots of Amaroo, is consistent with the belief that Amaroo, although presenting above average tolerance to chilling, is more cold-sensitive than Quila 66304. DBI has been used as a screening parameter for enhanced tolerance to high (Liu and Huang 2004) and low (Gerloff et al 1966) temperature, salt (Elkahoui et al 2004) and heavy-metal (Poznyak et al 2002) stress, besides aging (Zabrouskov et al 2002). Thus, findings from this study indicate that 18 carbons FAs DBI for roots might be a good tool for cold-tolerance screening of rice accessions.…”
Section: Effect Of the Cold Exposure On The Double-bond Index (Dbi)mentioning
confidence: 69%
“…The largest increase in DBI found for roots of Quila 66304, compared to roots of Amaroo, is consistent with the belief that Amaroo, although presenting above average tolerance to chilling, is more cold-sensitive than Quila 66304. DBI has been used as a screening parameter for enhanced tolerance to high (Liu and Huang 2004) and low (Gerloff et al 1966) temperature, salt (Elkahoui et al 2004) and heavy-metal (Poznyak et al 2002) stress, besides aging (Zabrouskov et al 2002). Thus, findings from this study indicate that 18 carbons FAs DBI for roots might be a good tool for cold-tolerance screening of rice accessions.…”
Section: Effect Of the Cold Exposure On The Double-bond Index (Dbi)mentioning
confidence: 69%
“…The authors concluded that the changes in the DB index were observed before the clinical manifestations, showing its potential as a prognostic tool for clinical practice [19]. Some other diseases where the DB index has been related with the evolution of the illness and the effect of the treatment include cancer [20], diabetes [14], exposition to hexavalent chromium [21], as well as inflammatory processes [22]. In these cases, the DB index resulted in a powerful tool to adjust the therapeutic treatment, according to the individual needs of the subjects under treatment.…”
Section: Double Bond Index (Db Index)mentioning
confidence: 99%
“…Poznyak et al . ( 2002 ) found that exposure to Cr (VI) induced lipid oxidation, which again can be detected by ozonation and quantitatively calculated by the DB-index and DB cell -index determination in plasma, erythrocytes, and sperm, and hence the ozonation method can be considered an acceptable modern technique (fast, inexpensive and simple) for chromium toxic effect monitoring in vitro .…”
Section: Biological Monitoring For Hexavalent Chromiummentioning
confidence: 99%